Fresh And Hardened Properties of Concrete Containing Ceramic Tile Waste as Coarse Aggregate and Glass Waste as Fine Aggregate - Ali, Asif; Ali, Sajjad; Ahmed Soomro, Faheem; Kerio, Manthar Ali (Journal of Structural Monitoring and Built Environment, 2022)
This study focused on the recycling of Glass Waste (GW) and Ceramic Tile Waste (CTW) in the concrete. However, GW was considered as fine aggregate replacement and CTW was considered as coarse aggregate replacement in the concrete. The concrete of grade 20 (M20) was prepared in the laboratory with various proportions of waste materials. The GW was introduced with 5%, 10%, and 15% replacement of fine aggregates, and CTW was incorporated with 10%, 20% and 30% replacement of coarse aggregates in the concrete. After that, fresh mix and hardened properties of concrete were evaluated. It was noticed that the with increases the partial replacement of GW as FA slump value increases. Glass waste particles absorbed less water as compared to natural FA and thus improving the workability of concrete. Based on the compressive strength results of 28days the optimum replacement was noticed as fine aggregate with 10% GW and coarse aggregate with 20% CTW. However, combined use of both wastes materials could not improves the strength performances of concrete significantly.